Competências demandadas pelo mercado do norte do brasil para a formação do engenheiro de produção - Silva, Gildemberg da Cunha (Universidade do Vale do Rio dos Sinos, 2016)
From the market view of production engineering in the North of Brazil, this study has the general objective to identify the skills demanded by sectors of industry and services in the formation of a production engineer. The advance of agribusiness in northern Brazil and the installation of large companies in the food industry and technology in the region are demanding for professionals with skills and expertise in the areas and sub-areas of activity of the production engineer, fostering advent professionals (accountants, economists, managers and engineers) from different areas of Brazil. In this sense, it sought to provide the knowledge and skills that production engineering courses of Higher Education Institutions (HEIs) from the northern region of Brazil has prioritized and have the skills and abilities that companies / North industries are demanding this professional . Research raised pointed out that the teaching of skills, focusing on professional training emerged in the mid 60 and 70. In this regard the priority powers should dialogue with human intelligence and the most diverse areas of knowledge and, above all, with the market . They interviewed 08 coordinators of course IES production engineering of the region and applied research in 43 companies in the North of Brazil. One of the lack of professional factors is given by the lack of training centers that meet the market needs of northern Brazil. In the specific case of the production engineer, there is still a great lack of potential areas of activity of the production engineer in northern Brazil. Future research may discuss the curricula adopted in engineering courses production of Northern Brazil.
Keywords: Ensino por competência; Ensino de engenharia; Formação do engenheiro de produção; Teaching competency; Engineering education; Formation of the production engineer; ACCNPQ::Engenharias::Engenharia de Produção